Impact Behaviour of Aluminum Particles upon Aluminum, Magnesium, and Titanium Substrates using High Pressure and Low-Pressure Cold Spray - Manap A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
aluminum; high pressure; low pressure; magnesium; residual stress; titanium